Teachers’ Barriers to ICT Integration in English Language Teaching: A Case Study at an Inclusive Junior High School - Novita Cahya Ramadhan; Sarlita D. Matra (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2026)
The integration of Information and Communication Technology (ICT) in English Language Teaching (ELT) has become essential in modern education. Despite the benefits, many teachers still face significant barriers when using technology in classroom instruction, particularly in inclusive school settings. This study aimed to investigate the barriers that English teachers face in integrating ICT at SMP N 10 Pekalongan, an inclusive junior high school where technology use remains minimal. A qualitative case study design was employed. Data were collected through semi-structured interviews with two English teachers, non-participant classroom observations, and document analysis of lesson plans. The data were analyzed using thematic analysis, guided by Ertmer's and Bingimlas's barrier frameworks, TPACK, and SAMR. The findings revealed that the main barriers were first-order, particularly limited devices, an unstable internet connection and a lack of ICT training for one of the teachers. Second-order barriers were minimal, as both teachers displayed positive attitudes and high levels of confidence. The level of ICT implementation reached the 'Modification' level of the SAMR model. Technical issues, for example video buffering due to an unstable internet connection, disrupted the flow of the classroom, and some students appeared not to take the lessons seriously. This study concludes that inclusive schools with low technology adoption should prioritise addressing first-order barriers before expecting transformative technology integration at the Redefinition level of SAMR.